Managing for Sustainable Development Impact - Kusters, Cecile; Batjes, Karen; Wigboldus, Seerp; Brouwers, Jan; Baguma, Sylvester Dickson (Practical Action Publishing Ltd, 2017)
This guide is about managing development initiatives and organizations towards sustainable development impact. It builds on the work of Guijt and Woodhill in the 2002 IFAD publication Managing for Impact in Rural Development: A Guide for Project M&E. Since then, the managing for sustainable development impact (m4sdi) approach has evolved with insights and feedback from CDI colleagues, clients, partners, and over 800 people who have been trained in its use. In addition, the authors have drawn on the work of many others. m4sdi is an integrated, results-oriented management approach, which can be used across a range of sectors and domains in a variety of contexts, and aims to contribute towards the Sustainable Development Goals (SDGs). It seeks to integrate ideas and practices from a range of approaches and methodologies for planning, monitoring and evaluation, using appropriate methods or tools that engage people in a process of learning and adaptation. It is specifically aimed at strengthening the readiness of leaders, decision-makers and development practitioners to effectively manage their initiatives/organizations in complex settings. m4sdi belongs to a special niche of management approaches, providing relevant perspectives on what makes for effective management for those directly involved in managing initiatives/organizations and wider groups of stakeholders. Many of the people trained in m4sdi have become believers and practitioners of the approach because it addresses several of the most serious concerns in development, such as the difficulty in reaching primary stakeholders, designing effective strategies and related monitoring and evaluation (m&e), focusing on capacity development and change management, and achieving sustainable development impact. The strength of m4sdi lies in its people-centred approach and how it seeks to integrate management processes within a complex environment. The evolvement of the approach needs to be documented to share lessons learned and support capacity development. And so the principles and practices covered in this guide relate to a variety of development initiatives/organizations in the fields of agriculture, food security, local economic development, value chains, enterprise development, and ecosystem governance. Much of the discussion takes place within the often complex context of development. As such, the guide aims to find a good balance between comprehensiveness and the principle of ‘less is more’.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia